DINAMIKA PEREKONOMIAN MASYARKAT MINANGKABAU: PELUANG DAN TANTANGAN PERDAGANGAN DI DAERAH RANTAU PARIAMAN ABAD XIX - Siti Aisyah (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2020)
This paper discusses the opportunities and challenges of trade in the rantau Pariaman area during the XIX century because this area was once known as a successful trading community that cannot be matched by its current society. The method used is historical research methods with data techniques through literature study. The success that was obtained was due to the fact that in the region's position it was an important route for world trade, the people were also able to take advantage of opportunities that could facilitate and facilitate them to achieve success during the colonial period. An elite group consisting of village officials and traditional leaders in the Netherlands as regulators in running the government. In addition, the people were able to make local products such as sea fish, salt, and coconut products that were very popular at that time. If viewed from the conditions at that time there were not a few challenges in the community in carrying out trading activities. The condition of the government was not friendly to the interests of the lower class people which resulted in frequent riots with the Dutch, because the people were not satisfied with the Dutch actions that always interfered in their affairs. In addition, the development of transportation tools such as trains and sailboats has made the Pariaman area market less crowded with outside traders and added to the absence of regeneration that can pass on the trade knowledge so that there is no more professional next generation of traders.